Analysis of Shear Stress on Flow around Sudden Accelerated Plate (Stokes’ First Problem) - Sudarma, Andi Firdaus (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2023)
Stokes' First Problem, often referred to as the